Incidence of Pathogens in Fruits and Vegetables in Tropical Bwari Town - Esumeh, Comfort Omogor; Andrew, Reigns (Universitas Airlangga, 2024)
Introduction: In numerous tropical regions of developing nations, the prevalence of foodborne illnesses is perceived to be more severe than in developed countries, due to insufficient food safety initiatives or the lack of a structured institutional framework for street food vendors. The study's objectives of examining microorganisms associated with fruits and vegetables, the prevailing temperature and the hygiene practices of various fruit and vegetable sellers were all met. Methods: A self-designed questionnaire completed by twenty vendors were used. Laboratory techniques like serial dilution, biochemical testing, and culture techniques were used. A handheld thermometer was used to determine the prevailing temperature, and descriptive statistics using Microsoft Excel was used to analyze data. Results and Discussion: Statistical analysis revealed that 80% of vendors had washing facilities, 70% worked in a clean environment, 20% washed their hands before handling fruits, 70% dressed correctly, and 70% kept their fruits and vegetables above the WHO temperature standard. A laboratory investigation revealed the bacteria counts of (watermelon being the highest 8.3×105, cucumber 5.4×105, carrot 2.3×105, orange 3.7×105). Microbial species encountered were Staphylococcus aureus, Escherichia coli, Salmonella species, amongst others, which increases health risk. Conclusion: The study concluded that temperatures, handling processes, and inadequate hygiene all had impact on fruits and vegetables sold in tropical Bwari area. It also established a link between temperature and the prevalence of bacteria in fruits and vegetables. As a result, the study suggests monitoring and surveillance of fruit and vegetable sellers, national vendor hygiene policies and public awareness.